Weight loss in heart failure is associated with increased mortality only in non‐obese patients without diabetes. Issue 6 (9th August 2019) - Niedziela, Jacek T.; Hudzik, Bartosz; Strojek, Krzysztof; Poloński, Lech; Gąsior, Mariusz; Rozentryt, Piotr
Abstract: Background: Weight loss (WL) is an independent predictor of mortality in patients with heart failure (HF). Moderate WL is recommended for overweight or obese patients with type 2 diabetes mellitus (DM). The aim of this study was to assess the prognostic impact of body weight reduction on survival in patients with both HF with reduced ejection fraction (HFrEF) and DM. Methods: The study comprised patients with HFrEF at the outpatient clinic. WL was defined as a body weight reduction of at least 7.5% during at least 6 months. Clinical features and 1 year mortality were analysed in WL and DM groups. Multivariate regression model was chosen to assess the predictive role of WL in HF patients with and without DM. The analysis regarding obesity before HF was also performed. Results: The study comprised 777 patients with HFrEF. Mean age was 53.2 ± 9.2, 12.0% were women, mean EF was 23.7 ± 6.0 %, and New York Heart Association III or IV class, DM, and WL were found in 60.5%, 33.3%, and 47.1% patients, respectively. WL was more prevalent in diabetic patients, comparing with those without DM (53.7% vs. 43.8%, respectively, 0.01), and was associated with higher 1 year mortality only in non‐diabetic group (17.6% for WL vs. 8.2% for non‐WL, log‐rank 0.001). In the multivariate analysis, WL was associated with a higher risk of 1 year mortality in non‐diabetic patients: HR 1.76 (1.05–2.95), 0.03 and only in the subgroup without obesity: HR 2.35 (1.28–4.32), 0.006. In non‐diabetic patients with obesity and in diabetic patients regardless of weight status, WL was not associated with worse prognosis (thereof, WL was excluded from the multivariate models). Conclusions: Overall, WL in HFrEF has emerged as a predictor of unfavourable outcomes only in non‐obese patients without DM. More importantly, this study has identified that the presence of DM (irrespective of weight status) or the presence of obesity in non‐diabetic patients abolished the unfavourable impact of WL on long‐term outcomes.